2016
DOI: 10.4103/0974-1208.178635
|View full text |Cite
|
Sign up to set email alerts
|

Association of large scale 4977-bp "common" deletions in sperm mitochondrial DNA with asthenozoospermia and oligoasthenoteratozoospermia

Abstract: OBJECTIVE:To determine the association of large-scale mitochondrial DNA (mtDNA) deletions with abnormal sperm or abnormal flagellar movement of human spermatozoa in asthenozoospermia and oligoasthenoteratozoospermia (OAT) subjects using percoll gradients fractionation and long-range polymerase chain reaction (PCR).DESIGN:We investigated sixty infertile men and thirty normal healthy fertile controls. Of sixty infertile men, 39 were asthenozoospermia and 21 were OAT.MATERIALS AND METHODS:Percoll gradients discon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 21 publications
1
10
0
Order By: Relevance
“…Next, to replicate findings from previous publications (Kao et al, 1995; 1998; St John et al., 2001; May-Panloup et al, 2003; Song and Lewis, 2008; Ieremiadou and Rodakis, 2009; Gholinezhad Chari et al., 2015; Ambulkar et al, 2016A; Ambulkar et al, 2016B; Zhang et al, 2016; Gabriel et al, 2012; Mughal et al, 2017; Bahrehmand Namaghi and Vaziri, 2017; Talebi et al, 2017), we examined the associations of mtDNAcn and mtDNAdel with semen parameters. The mean difference (MD) and 95% confidence intervals (CI) from the age and batch adjusted generalized linear models comparing semen parameter values by quartiles of sperm mtDNAcn and mtDNAdel are presented in Table 2.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Next, to replicate findings from previous publications (Kao et al, 1995; 1998; St John et al., 2001; May-Panloup et al, 2003; Song and Lewis, 2008; Ieremiadou and Rodakis, 2009; Gholinezhad Chari et al., 2015; Ambulkar et al, 2016A; Ambulkar et al, 2016B; Zhang et al, 2016; Gabriel et al, 2012; Mughal et al, 2017; Bahrehmand Namaghi and Vaziri, 2017; Talebi et al, 2017), we examined the associations of mtDNAcn and mtDNAdel with semen parameters. The mean difference (MD) and 95% confidence intervals (CI) from the age and batch adjusted generalized linear models comparing semen parameter values by quartiles of sperm mtDNAcn and mtDNAdel are presented in Table 2.…”
Section: Resultsmentioning
confidence: 90%
“…Studies comparing sperm fractions based on motility from gradient centrifugation reported that, within individuals, sperm fractions with poorer motility have higher frequencies of mtDNA deletions compared with sperm fractions with higher motility (Kao et al, 1995; Kao et al, 1998; Ieremiadou and Rodakis, 2009; Gholinezhad Chari et al., 2015; Ambulkar et al, 2016a; 2016b), with one exception (St John et al, 2001), which may have been driven by a limited sample size. Similarly, studies of men from different geographic regions, including the USA (Song and Lewis, 2008), England (St John et al, 2001), Greece (Ieremiadou and Rodakis 2009), Taiwan (Kao et al., 1995; Kao et al., 1998), Turkey (Mughal et al, 2017), Iran (Bahrehmand Namaghi and Vaziri, 2017; Talebi et al, 2017), and India (Ambulkar et al, 2016A) reported that sperm mtDNAdel were more frequent among men classified as infertile based on abnormal semen parameters compared with men with normal semen parameters. Investigators of an Australian study, however, did not observe higher mtDNAdel among men with oligospermia or azoospermia compared with men with normospermia (Cummins et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…If the mtDNA 4977 deletion occurs during spermatogenesis and/or spermiogenesis, the mature spermatozoa are endowed with dysfunctional mitochondria, which can act as a source of ROS. Interestingly, mtDNA 4977 has been recorded in the spermatozoa of infertile males with asthenozoospermia and oligoasthenozoospermia [148,149]. An alternative large-scale mtDNA deletion comprising 7436 bp (mtDNA 7436 ) has also been reported in low-motility human spermatozoa [150].…”
Section: Sperm Dna Modificationsmentioning
confidence: 99%
“…[ 9 15 ] Recently, mitochondrial dysfunction reported in AZS men came to attention, several studies reported this dysfunction is related to idiopathic asthenozoospermia, since sperm motility is regulated by intrinsic factors, and requires an appropriate supply of adenosine triphosphate. [ 16 18 ] For adenosine triphosphate synthesis, these gradients are generated by electron transfer maintained by the inner mitochondrial layer. Then energy storage in mitochondria is related to proton concentration and electric potential gradient in cell membrane.…”
Section: Introductionmentioning
confidence: 99%